Kekerasan Seksual dalam Naskah Sabhaparwa Merapi-Merbabu: Analisis Wacana Kritis terhadap Narasi Patriarkal - Galang Adhi Pradipta; I Made Suparta (Masyarakat Pernaskahan Nusantara, 2025)
Sexual violence is a persistent historical issue recorded in the Sabhaparwa manuscript (31 L 92) from the Merapi-Merbabu scriptorium. Using Fairclough’s critical discourse analysis, Foucault’s power relations, and Butler’s gender performativity, this study investigates Draupadi’s violation as a critique of state law (Rajadharma). Micro-analysis reveals a tiered construction of violence exposing the perpetrators'